QuantiFERON test interpretation in patients receiving immunosuppressive agents: an alert. Issue 4 (6th April 2017) - Belliere, Julie; Blancher, Antoine
Latent tuberculosis infection (LTBI) diagnosis in immune-mediated inflammatory diseases is complex because of the patient characteristics and the imperfection of available tests [1]. Functional T-cell assays are exposed to bias at several levels (manufacturing, pre-analytical, analytical and immunological) [2] and, unfortunately, the lack of a gold standard precludes higher diagnostic accuracy. However, the QuantiFERON GOLD In-tube test (QFT; QIAGEN, Hilden, Germany) represents a largely used and modern alternative to the tuberculin skin test. Even if performance specifications of QFT are of great interest (specificity of 99% and sensitivity of 84%) [3], some patients remain with an "indeterminate result" because of failed positive control corresponding to the incapacity of lymphocytes to secrete interferon (IFN)-γ after 24 h of stimulation by phytohemagglutinin A (PHA). Caution to patients with negative QuantiFERON and low mitogen response receiving immunosuppressive agents http://ow.ly/MKsP308O3jo